Towards the specification of windows sizes for natural ventilation in classrooms in a warn climate, Nigeria - M.B., Olufowobi; O.A., Adenuga (Penerbit UKM, 2012)
The paper presents a fundamental approach to the establishment of window sizes, essentially to facilitate (achieve) the promotion air movement in classrooms. A procedure that entailed the analysis of prevailing climatic conditions in relation to the thermal comfort requirement of classroom users has been used to establish some design parameters for windows. The parameters, which are areas of openings and orientation of windows, are basic to the design of classrooms for which adequate air movement is an essential requirement for achieving thermal comfort of pupils. The procedure and results can find relevance as aids or input in the design of classrooms and for policy makers charged with the responsibility of providing space facilities for basic education in the country. On another application, the procedure and results can also be sued to estimate the likely average air speeds in existing classrooms, or classroom on the drawing board, when the relevant parameters of outdoor wind speed, wind direction, areas of window openings window orientation are known.